2012
DOI: 10.3109/10715762.2012.733003
|View full text |Cite
|
Sign up to set email alerts
|

Role of physiological levels of 4-hydroxynonenal on adipocyte biology: implications for obesity and metabolic syndrome

Abstract: Lipid peroxidation products such as 4-hydroxynonenal (HNE) are known to be increased in response to oxidative stress, and are known to cause dysfunction and pathology in a variety of tissues during periods of oxidative stress. The aim of the current study was to determine the chronic (repeated HNE exposure) and acute effects of physiological concentrations of HNE towards multiple aspects of adipocyte biology using differentiated 3T3-L1 adipocytes. Our studies demonstrate that acute and repeated exposure of adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
5
18
0
Order By: Relevance
“…The increased catalase activity in 4-HNE treated differentiating preadipocytes was more significant in IS-derived cells, suggesting higher sensitivity to 4-HNE-induced oxidative stress, compared to IR-derived counterparts. Taken together, our data confirm both earlier in vitro findings of increased ROS production in response to 4-HNE in 3T3L-1 preadipocyte cell line [26] and in vivo observations of elevated ROS scavenging enzymes in adipose tissues from obese subjects with increased 4-HNE levels [17], adding to the significant role 4-HNE plays in modulating adipose tissue homeostasis.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…The increased catalase activity in 4-HNE treated differentiating preadipocytes was more significant in IS-derived cells, suggesting higher sensitivity to 4-HNE-induced oxidative stress, compared to IR-derived counterparts. Taken together, our data confirm both earlier in vitro findings of increased ROS production in response to 4-HNE in 3T3L-1 preadipocyte cell line [26] and in vivo observations of elevated ROS scavenging enzymes in adipose tissues from obese subjects with increased 4-HNE levels [17], adding to the significant role 4-HNE plays in modulating adipose tissue homeostasis.…”
supporting
confidence: 80%
“…Therefore physiological levels of 4-HNE (up to 10 µM) in adipose tissues play a crucial role in redox homeostasis, whereas elevated 4-HNE levels (above 10 µM) can cause adipocyte dysfunction and insulin resistance [26,39]. This study reports for the first time Emerging data initially showed that elevated levels of 4-HNE in SC adipose tissues are located mainly within adipocytes and blood vessels in comparable levels between IS and IR subjects.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Rald has been shown to inhibit PPARγ activation . Hydroxynonenal is another ALDH1A1 substrate (low affinity), which can also inhibit lipid accumulation . Thus, ALDH1A1 function suggests a lipid‐dependent mechanism for regulation of energy homeostasis in xenocultures.…”
Section: Discussionmentioning
confidence: 99%